2011
DOI: 10.1097/brs.0b013e3181fc1aff
|View full text |Cite
|
Sign up to set email alerts
|

Disc Replacement Adjacent to Cervical Fusion

Abstract: The porous-coated motion cervical prosthesis restored the ROM of the treated level to the intact state. When the porous-coated motion prosthesis was used in a hybrid construct, the TDR response was not adversely affected. A hybrid construct seems to offer significant biomechanical advantages over two-level fusion in terms of reducing compensatory adjacent-level hypermobility and also loads required to achieve a predetermined ROM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…However, only 1 type of hybrid surgery was investigated [ 9 ]. Lee et al [ 12 ], in a biomechanical study of 2 approaches of hybrid surgery using 3 cadaveric cervical spines, showed that the location of the single-level fusion, above or below the arthroplasty, did not significantly affect the ROM and could reduce hypermobility in adjacent-level. Cho et al[ 10 ] used cadaveric spine specimens to explore biomechanics under a compressive load after 2 types of hybrid surgery; results demonstrated no significant change in ROM at adjacent levels or in the entire cervical spine when comparing both types of surgery with the intact spine.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 1 type of hybrid surgery was investigated [ 9 ]. Lee et al [ 12 ], in a biomechanical study of 2 approaches of hybrid surgery using 3 cadaveric cervical spines, showed that the location of the single-level fusion, above or below the arthroplasty, did not significantly affect the ROM and could reduce hypermobility in adjacent-level. Cho et al[ 10 ] used cadaveric spine specimens to explore biomechanics under a compressive load after 2 types of hybrid surgery; results demonstrated no significant change in ROM at adjacent levels or in the entire cervical spine when comparing both types of surgery with the intact spine.…”
Section: Discussionmentioning
confidence: 99%
“…ROMs of our FEMs in flexion-extension, lateral bending, and axial rotation were compared with the data from previous studies [8,[18][19][20]. The ROMs of the intact FEMs at C2/3, C3/4, C4/5, C5/6, and C6/7 were 4.11°± 0.75°, 5.22°± 1.10°, 5.74°± 1.08°, 5.70°± 1.11°, and 4.39°± 0.94°, respectively, in flexion; 3.24°± 0.79°, 4.23°± 1.03°, 4.65°± 1.01°, and 4.04°± 1.03°, respectively, in extension; 5.15°± 0.85°, 4.84°± 1.15°, 4.73°± 1.29°, 3.42°± 0.77°, and 2.63°± 0.58°, respectively, in lateral bending; and 2.04°± 0.83°, 2.97°± 0.79°, 3.73°± 0.67°, 3.14°± 0.62°, and 2.20°± 0.93°, respectively, axial rotation (Fig.…”
Section: Validation Of the Intact Femsmentioning
confidence: 99%
“…[36] The selection of optimal surgical treatment for CSM, especially for multilevel cervical spondylotic myelopathy (mCSM), remains controversial. [19] Surgeries mainly involved anterior and posterior approaches, including anterior cervical discectomy and fusion (ACDF), [1012] anterior cervical corpectomy and fusion (ACCF), [1115] laminoplasty, [1620] laminectomy, [12,1822] and laminectomy with fusion. [2023] ACDF for treating CSM was firstly introduced by Smith and Robinson [24] and Cloward [25] ; the anterior procedure has become the most widely used surgical choice.…”
Section: Introductionmentioning
confidence: 99%